Pengelolaan Supply Produk Waferstick dengan Mempertimbangkan Kapasitas Produksi dan Persediaan Barang Jadi di PT. Tiga Pilar Sejahtera Food,Tbk - -, Yuniaristanto; Aisyati, Azizah; Hariyanto, Tri (Performa: Media Ilmiah Teknik Industri, 2007)
In general, planning supply use the information from combination varying capacity and inventory to plan the aggregate rates of production by time period for groups of product. This research objective is PT. Tiga Pilar Sejahtera’s (TPS) that produces wafersticks. In the company sometimes occured the wafersticks product can be not fulfilled. This is happened because waferstick inventory unstable. This causes problems that PT. Tiga Pilar Sejahtera (TPS) was less capable to fulfill the market’s demands. To solve this PT TPS should be managing the working hours, workforces, production capacity and finished goods inventory, they are called aggregate planning. This research are determine safety stocks, planning supply and material inventory planning.Managing supply of waferstick product is started by forecast the demand. The forecast result is used to estimate safety stock of waferstick. Then the forecasting result and safety stock become of input Integer linier programming model to determine aggregate planning. The aggregate planning is used to find optomal lot size of waferstick raw material. Then lot sizing become input Planned Order Receipt in the Material Planning Requirements (MRP). Forecast method used to forecast the demand is decomposition, this method is he best method find estimation demand because it have more less MAD than the other. The determination of the safety stock is actually more accurate with the 90% by Romy & Yuli waferstick safety inventory is 1106 cartons and 2364 cartons for Pio. From aggregate planning there is back order in 13 th is 11 cartons. The planning cost for Romy & Yuli waferstick Rp 625.670.902,33 and Cost for Pio waferstick Rp 1.462.296.180,00. Waferstick material planning by optimal lot size between 695 kilograms up to 8487 kilograms by waferstick materials cost is Rp 6.315.520,00.